Zwischen Kunst, Kult und Kollaboration: der deutsche kirchennahe "Kunst-Dienst" 1928 bis 1945 im Kontext - Kusske, Dieter (Staats- und Universitätsbibliothek Bremen, 2013)
Kunst-Dienst, Avant-garde, Aesthetics , Bauhaus, German work-association, Design discourse, Protestant Church, Expressionism, Handicraft, Fight between church and state, Reform movement run by the church, Nazism and modernization, Degenerate art, Religious art, Secularization, New objectivity. - There are three main aspects the Kunst-Dienst (KD), which was founded in Dresden in February 1928, tried to teach until the thirties of the twentieth century: the religious-humanistic understanding of the world; a religious universal aim according to Paul Tillich´s Theory of cultural theologie (Kulturtheologie); the belief in a reform movement run by the Church in accordance with the progress in mastering nature and technology in the world of life, work and art; modern aesthetic approaches of Expressionism, New Objectivity (Neue Sachlichkeit) and Deutscher Werkbund, aiming at reforming culture.So the KD with its art-teaching work could partly act as a supporter of an avant-garde. It tried to achieve qualifying and updating of the religious- clerical relation to modern arts and fought for modern architecture and industrial design. As an institution that had been personally, organizationally, economically and politically integrated into the Nazi Regime since 1933, the KD was not only used as an element for the establishment of an apparently attractive variety in the production, distribution and reception of art. Also in its art-teaching work, it can be seen as an example of "different", "right-wing" avant-garde, "useful", "conservative" or even "reactionary" modern art.